Marmion : a Tale of Flodden Field - Scott, Walter, 1771-1832 (Scott, Walter, 1771-1832. Poems. 2018, 2018)
The critical apparatus in this volume includes an extended essay on the development of the text, a Historical Note, Explanatory Notes and a full glossary of Scots, foreign and archaic words.